Outside Back Cover: Volume 2 Issue 2. (29th June 2021) - Qi, Haoyuan; Liang, Baokun; Kaiser, Ute
Abstract : Outside back cover image : As the astronomers chase the biggest questions in the universe, such as planets and stars, microsopists are dedicated to observing the smallest objects down to the atomic scale. Thanks to the advancement of electron optics, modern transmission electron microscopes can readily reach sub‐Ångstrom resolution. However, even with the best instruments at hand, revealing the atomic structures of twodimensional polymers and covalent organic frameworks remains a significant challenge. The difficulty arises from the so‐called electron radiation damage. Upon electron illumination, the tiny "shooting stars" fiercely bombard the specimen leading to rapid structural degradation of the organic crystals. The mechanisms and circumvention of electron radiation damage, particularly on covalent organic crystals, will be discussed in this Perspective. (DOI: https://doi.org/10.1002/smm2.1035 )